Islamic Religious Education Learning Strategy - Etika Pujianti; Latifatul Mutoharoh; Binti Wahidatussa'diyah; Maya Sari; Siti Padilah; Rizki Maulana (Civiliza Publishing, Indonesia., 2026)
Islamic Religious Education (PAI) plays a strategic role in shaping students' character to become faithful, pious, and morally upright individuals. However, in practice, PAI learning still faces various challenges, such as the dominance of conventional teaching methods, low student participation, and a lack of innovation in the use of instructional strategies. This study aims to analyze effective PAI learning strategies, including approaches, models, methods, and their implementation in improving the quality of learning in the modern era. This research employs a qualitative approach using a library research method, drawing on books, scientific journals, and other relevant references. The findings indicate that effective PAI learning strategies must integrate contextual, humanistic, and spiritual approaches, and be supported by active learning models such as cooperative learning, problem-based learning, and inquiry learning. In addition, the utilization of educational technology is a crucial factor in enhancing learning effectiveness. In conclusion, the success of PAI learning is highly dependent on teachers' creativity in designing innovative, adaptive, and relevant strategies in accordance with contemporary developments